Cognitive Effects and Sedation. Issue 1 (October 2015) - Dhingra, Lara; Ahmed, Ebtesam; Shin, Jae; Scharaga, Elyssa; Magun, Maximilian
Abstract Objective Cognitive effects and sedation (CES) are prevalent in chronic nonmalignant pain populations receiving long‐term opioid therapy and are among the most common reasons patients discontinue opioid use. In this narrative review, we describe the phenomenology, epidemiology, mechanisms, assessment, and management of opioid‐related CES. Design We reviewed the empirical and theoretical literature on CES in opioid‐treated populations with chronic pain. Data on long‐term opioid therapy (≥3 months in duration) in chronic nonmalignant pain patients were sought. Results The phenomenology of CES includes: inattention, concentration difficulties, memory deficits, psychomotor dysfunction, perceptual distortions, and executive dysfunction and somnolence, sleep disorders, and lethargy. Deficits may be caused by unrelieved pain or opioid therapy alone, or from a combination of these and other factors. Mechanisms include central nervous system effects, for example, direct toxic effects on neurons resulting in decreased consciousness; direct effects on processing and reaction resulting in cognitive or psychomotor impairment, and inhibitory effects on cholinergic activity. Pharmacological management approaches may include opioid dose reduction and rotation or psychostimulant use. Nonpharmacological approaches may include cognitive‐behavioral therapy, mindfulness‐based stress reduction, acupuncture, exercise, and yoga. Conclusions The most prevalent CES include: memory deficits (73–81%), sleep disturbance (35–57%), and fatigue (10%). At its most severe, extreme cognitive dysfunction can result in frank delirium and decreased alertness can result in coma. Emotional distress, sleep disorders, and other comorbidities and treatments can worsen CES, particularly among the elderly. Conclusions about the neuropsychological domains affected by opioids are limited due to the heterogeneity of studies and methodological issues.